Integrating China into the global economy - Lardy, Nicholas R. (Brookings Institution Press, 2002)
Annotation "China's accession to the World Trade Organization (WTO) has been hailed as the biggest coming-out party in the history of capitalism. Its membership eventually will contribute to higher standards of living for its citizens and increased growth for its economy. But why would the Chinese communist regime now voluntarily agree to comply with the many complex rules of the global trading system? China has already become the world's seventh largest trading country while avoiding these constraints by remaining outside the system." "The answer to this question forms the basis for this book. Drawing on a wealth of scholarship and experience, Nicholas R. Lardy explores the many pressures on the Chinese government to comply with the standards of the rules-based international trading system. Lardy explains how China's leadership expects to leverage the increased foreign competition inherent in its WTO commitments to accelerate its domestic economic reform program, leading to the shrinkage and transformation of inefficient, money-losing companies and hastening the development of a commercial credit culture in its banks."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved